Experiences of physical violence by women living with intimate partners - F.C. Madzimbalale; L.B. Khoza (AOSIS, 2010)
Intimate partner violence directed towards females by male partners is a common significant global public health problem. Most victims of physical aggression such as women and children are subjected to multiple acts of violence over extended periods of time, suffering from more than one type of abuse, for example physical which is more symbolic and evidenced by scars. The purpose of this study is to increase understanding of the symbols of physical violence as experienced by women who live with intimate partners in the Vhembe district of the Limpopo Province. The research design of this study was qualitative, exploratory and descriptive in nature. The accessible population was those participants who used the trauma unit A in a particular hospital. Seven women comprised the sample of the study. In-depth individual interviews were conducted exploring the women's experiences in the context of physical violence. From the data collected all seven participants experienced some form of physical violence which resulted in permanent deformity. They experienced some form of battering such as kicking, stabbing, burning, fracturing, strangling and choking. Recommendations were made that health care providers are encouraged to implement screening for physical violence, to provide appropriate interventions if assault is identified and to provide appropriate education regarding, employment opportunities, legal literacy, and rights to inheritance. Human rights education and information regarding domestic violence should be provided to them because this is their absolute right (UNICEF, 2000:14).